USAHA PENINGKATAN STATUS GIZI BALITA POSYANDU â€DELONIX REGIAâ€ DI KELURAHAN LASIANA KUPANG MELALUI PEMANFAATAN PEKARANGAN DENGAN BUDIDAYA SAYURAN ORGANIK DALAM SISTEM IRIGASI HEMAT AIR - Abdul Kadir Djaelani; Ali Hasan; Efendy Pasambuna (Politeknik Pertanian Negeri Kupang, 2008)
Improving Needs of Infantâ€™s Nutrient by Exploiting House Lawn for Cultivating Vegetables Organically U5sing Limited Water Irrigation System at Delonix Regia Posyandu, Lasiana-Kupang. This activity aimed to increase the read ability of Delonix Regia Posyandu participants to market opportunity, and to provide their skills capability in cultivating vegetables organically using limited water irrigation system, in order to increase their infant needs and family income. By this activity, the participants may provide high quality vegetables and fruits for people, increasing their income, retaining nutrient of their infant, and assisting local government in rising achievement of â€œTiga Batu Tungkuâ€ program (that is health, prosperity and education). The methods in this activity were discussion, learning by doing, and fieldtrip. The result indicated that the participants positively responded in cultivating vegetables organically with limited water on their house lawn for fulfillment needs of their infantâ€™s nutrient and their additional income. In the perspective of educational, social cultural and house lawn property, the participants following up this activity were 35%.Keywords: infantâ€™s nutrient, house lawn, vegetables